Faktor-Faktor yang Berhubungan dengan Kejadian Hipertensi di Wilayah Kerja Puskesmas Jati Luhur Bekasi Tahun 2018 - Maulidina, Fatharani (ARKESMAS [Arsip Kesehatan Masyarakat], 2019)
Abstract In Indonesia non-communicable diseases become a very serious health problem at this time, namely hypertension. Hypertension risk factors include irreversible factors (age, gender, family history) and modifiable factors (smoking, nutritional status, physical activity, stress, and food consumption) which are considered to greatly affect the incidence of hypertension. This study aims to determine the factors associated with the incidence of hypertension. This research is quantitative with cross sectional approach. Done in the work area of ??Jatiluhur Bekasi health center in July 2018. Data collection was carried out on 143 respondents who were patients who visited the work area of ??the puskesmas using questionnaires and direct measurements. Quota sampling technique. The analysis used is univariate and bivariate. Univariate test results showed the proportion of hypertensive patients mostly were ertensi 40 years (71.3%), female gender (57.3%), low education (61.5%), working (55.2%), having a history family (61.5), nutritional status with overweight and obesity (62.2%), non-smoking (50.3%), and mild physical activity (79.7%). The results of the bivariate test showed that the variables associated with the incidence of hypertension were age (Pvalue = 0,000), education (Pvalue = 0,000), work (Pvalue = 0,001), family history (Pvalue = 0,033), and nutritional status (Pvalue = 0,003), while variables that are not related to the incidence of hypertension, namely sex (Pvalue = 0.454), smoking (Pvalue = 1,000) and physical activity (Pvalue = 0.197). To reduce the occurrence of hypertension, there needs to be education to prevent such as providing counseling to the public about hypertension and conducting blood pressure checks regularly. Keywords: Hypertension, Risk Factors